KEANEKARAGAMAN JENIS-JENIS TANAMAN KOLEKSI DI KEBUN RAYA PURWODADI, BALI DAN CIBODAS YANG DISERANG BENALU Dendrophthoe pentandra (L.) Miq. (LORANTHACEAE) - Sunaryo, Sunaryo (Buletin Kebun Raya, 2010)
Botanic Garden represents an ecosystem area in which parasitic plants such as mistletoes are also incorporated. Mistletoe of Dendrophthoe pentandra (L.) Miq. (Loranthaceae) was a parasite of various plants cultivated in Botanic Gardens of Purwodadi, Bali, and Cibodas. The mistletoe attacked 143 host species which included in 48 plant families in those three Botanic Gardens. The most attacked host plants were belong to family Moraceae, especially Ficus spp., following by members of Myrtaceae, especially Syzygium spp. The ability to become parasite of various plants species assured that mistletoe of D. pentandra did not chosen certain host plants. The parasitic study of mistletoe D. pentandra is also reported in this paper.